MEDIAN AND ULNAR NERVE INJURIES REDUCE VOLITIONAL FORELIMB STRENGTH IN RATS - Meyers, Eric C. (Muscle Nerve, 2017)
INTRODUCTION: Peripheral nerve injuries (PNI) are among the leading causes of physical disability in the United States. The majority of injuries occur in the upper extremities, and functional recovery is often limited. Robust animal models are critical first steps for developing effective therapies to restore function after PNI. METHODS: We developed an automated behavioral assay that provides quantitative measurements of volitional forelimb strength in rats. Multiple forelimb PNI models involving the median and ulnar nerves were used to assess forelimb function for up to 13 weeks postinjury. RESULTS: Despite multiple weeks of task-oriented training following injury, rats exhibit significant reductions in multiple quantitative parameters of forelimb function, including maximal pull force and speed of force generation. CONCLUSIONS: This study demonstrates that the isometric pull task is an effective method of evaluating forelimb function following PNI and may aid in development of therapeutic interventions to restore function.